Fatty acid profile and assessment of heavy metals content of Sardina pilchardus captured in the Algerian coast - Benguendouz, Abdennour; Bouderoua, Kaddour; Bouterfa, Asma; Belabes, Mohamed; Bekada, Ahmed Mohammed Ali; Sioriki, E; Zabetakis, I (My University, 2017)
Total lipids, fatty acid composition and heavy metal content of Sardina pilchardus fillet samples captured in February 2014 in Beni saf, Mostaganem, Ghazaouet, Algiers and Jijet coast were evaluated. Total lipid content was related to the five sites of catch (p<0.05), ranging from 7.18 g 100g-1 for Algiers to 10.07g 100g-1 for Beni saf. The fatty acid composition of S. pilchardus shows a high content of polyunsaturated fatty acids (PUFAs) dominated by n-3 fatty acids eicosapentaenoic acid (EPA C20:5 n-3) and docosahexaenoic acid (DHA C22:6n-3) with maximum rates of 15.75% and 33.42%, respectively (p<0.05). The saturated fatty acid (SFA) content was important in different samples of sardines, ranging from 35.50% to 41.32% according to sites of capture (p<0.05). Concerning the heavy metals, the levels of lead (Pb) ranged from 0.013mg to 0.024mg, however those of mercury (Hg) varied from 0.080 mg to 0.130 mg (p<0.05), which affects the health value of the fish species.
Fatty acid profile and assessment of heavy metals content of Sardina pilchardus captured in the Algerian coast
Keywords: Algerian coast, Sardina pilchardus, Fatty acids, Lipids, Heavy metals